Análise comparativa de técnicas compensatórias de drenagem urbana nos municípios de Natal e Mossoró - Lima, Fellipe Elpidio Rodrigues Silva de (2022)
Brazil is a country with deficient drainage systems and, for the most part, can’t support the hydrological demands generated in large centers. Traditional systems can’t attend the high population increase and the growth of impervious areas. In the search for alternatives that consider concepts of long-term sustainability and the management of rainwater as a whole, compensatory techniques have emerged, which seek to reduce the impacts of urbanization, rescuing as close as possible the hydrograph in pre-urbanization conditions. Thus, this study aimed to evaluate the effectiveness of the applicability of compensatory techniques allied to the environmental conditions offered by the local region. The compensatory techniques analyzed were infiltration wells and detention reservoirs tanks implemented in four (4) standard lots in the municipalities of Natal and Mossoró, in the state of Rio Grande do Norte. The results showed that the performance of the reservoirs is less dependent on the environmental conditions, having very similar behaviors, presenting a 100% reduction in failures in the scenario with distributed rainfall. The infiltration wells, on the other hand, presented a different behavior due to the type of soil, impacting even the number of wells that each lot demanded, but also with significant reductions in the number of failures.